Pengaruh Media Leaflet tentang Perawatan Payudara terhadap Tingkat Pengetahuan Ibu Nifas di Puskesmas Limapuluh - Virginia De Retty Batubara; Yesi Septina Wati; Merita Herawati; Rifa Yanti (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Breast care is an essential component of postpartum care to maintain maternal breast health and prevent breast-related complications during the breastfeeding period. However, many postpartum mothers still have limited knowledge regarding appropriate breast care practices. Health education using leaflets is considered an effective educational strategy to improve mothers' knowledge. To analyze the effect of leaflet-based health education on the knowledge of postpartum mothers regarding breast care at Limapuluh Public Health Center, Pekanbaru City. This quantitative study employed a pre-experimental design with a one-group pretest–posttest approach. A total of 45 postpartum mothers were recruited using the total sampling technique. The intervention consisted of health education using a leaflet containing information on breast care. Knowledge was assessed before and after the intervention using a structured questionnaire. Data were analyzed using the Wilcoxon Signed Rank Test with a significance level of p < 0.05. Before the intervention, most respondents had poor knowledge (51.1%) with a mean score of 60.00. Following the intervention, 97.8% of respondents achieved good knowledge, and the mean knowledge score increased to 91.11. The Wilcoxon Signed Rank Test revealed a statistically significant difference in knowledge before and after the intervention (p < 0.001). Leaflet-based health education effectively improved postpartum mothers' knowledge of breast care and can be used as an educational medium to support maternal health promotion in primary healthcare settings.